Clinical effectiveness of care managers in collaborative care for patients with depression in Swedish primary health care: a pragmatic cluster randomized controlled trial - Cecilia Björkelund; Irene Svenningsson; Dominique Hange; Camilla Udo; Eva-Lisa Petersson; Nashmil Ariai; Shabnam Nejati; Catrin Wessman; Carl Wikberg; Malin André; Lars Wallin; Jeanette Westman (BMC Family Practice, 2018)
Abstract Background Depression is one of the leading causes of disability and affects 10-15% of the population. The majority of people with depressive symptoms seek care and are treated in primary care. Evidence internationally for high quality care supports collaborative care with a care manager. Our aim was to study clinical effectiveness of a care manager intervention in management of primary care patients with depression in Sweden. Methods In a pragmatic cluster randomized controlled trial 23 primary care centers (PCCs), urban and rural, included patients aged ≥ 18 years with a new (< 1 month) depression diagnosis. Intervention consisted of Care management including continuous contact between care manager and patient, a structured management plan, and behavioral activation, altogether around 6-7 contacts over 12 weeks. Control condition was care as usual (CAU). Outcome measures: Depression symptoms (measured by Mongomery-Asberg depression score-self (MADRS-S) and BDI-II), quality of life (QoL) (EQ-5D), return to work and sick leave, service satisfaction, and antidepressant medication. Data were analyzed with the intention-to-treat principle. Results One hundred ninety two patients with depression at PCCs with care managers were allocated to the intervention group, and 184 patients at control PCCs were allocated to the control group. Mean depression score measured by MADRS-S was 2.17 lower in the intervention vs. the control group (95% CI [0.56; 3.79], p = 0.009) at 3 months and 2.27 lower (95% CI [0.59; 3.95], p = 0.008) at 6 months; corresponding BDI-II scores were 1.96 lower (95% CI [− 0.19; 4.11], p = 0.07) in the intervention vs. control group at 6 months. Remission was significantly higher in the intervention group at 6 months (61% vs. 47%, p = 0.006). QoL showed a steeper increase in the intervention group at 3 months (p = 0.01). During the first 3 months, return to work was significantly higher in the intervention vs. the control group. Patients in the intervention group were more consistently on antidepressant medication than patients in the control group. Conclusions Care managers for depression treatment have positive effects on depression course, return to work, remission frequency, antidepressant frequency, and quality of life compared to usual care and is valued by the patients. Trial registration Identifier: NCT02378272. February 2, 2015. Retrospectively registered.